Roman Catholic Church and economic growth in 19th-century Ireland - Kennedy, Liam (Economic & Social Studies, 1978)
It has been claimed in both historical and contemporary writings that the activities of the Roman Catholic Church inhibited economic development in nineteenth-century Ireland. One specific line of reasoning has been that the Roman Catholic Church, by depriving the Irish economy of substantial flows of physical and human capital, thereby reduced the rate of economic growth. In this article the logical, theoretical, and empirical bases of such claims are challenged. A further cluster of arguments - that the character structure associated with Irish Catholicism is inimical to economic progress ? is also rejected. It is concluded that the role of the church in the context of Irish economic development has been a positive one.
Keywords: Catholic Church - Ireland; Religion - Economic aspects